The influence of green infrastructure attributes on house price / Nurul Nazyddah Mat Nazir - Mat Nazir, Nurul Nazyddah (Institute of Graduate Studies, 2017)
Today, environmental considerations have become crucial in each and every development plan and project. It is a vital approach in the 21st century. Due to the current environmental crisis, one vital approach is often emphasized to maintain and preserve the surrounding environment and this approach is referred to as the ‘Green Infrastructure Approach’. Green Infrastructure is commonly associated with the concept of sustainable development. It differs from grey infrastructure in that it emphasizes the network of green space in a particular area. Generally, an environment offers a variety of activities and benefits which are mostly unmeasurable. Hence, the Hedonic Pricing Model is one of the methods that is often exploited to reflect the environmental values of a surrounding area. This study looks at green infrastructure elements and how they affect housing prices. The Hedonic Pricing Model is used to calculate the value of environmental features or elements that affect housing price. However, it is limited in that it only measures the environmental benefits impacting the prices of houses and merely estimates people’s willingness to pay for these benefits. If people are unaware of their environment, the value is not reflected. This study allows the researcher to look into the following objectives: (a) to gauge the existing green infrastructure components in the study area; (b) to identify public preferences towards green infrastructure(s) in a housing area with the botanical garden being the main green infrastructure component in the study area and (c) to determine the new market equation of a house by adding the green infrastructure attributes using the Multiple Regression Hedonic Pricing Model (HPM)..